Some peculiarities of forming independent cooperation in the acitivities of senior preschoolers - Jacikevičienė , O. (Psichologija, 1987)
An experimental teaching of senior preschoolers was carried out with the purpose of improving the following parameters of their group activities: (l) preliminary distribution of functions, ( 2) leadership, ( 3) exactness of action, ( 4) activity rate, ( 5) speech communication, ( 6) general harmony of group activities. The teaching was based on the psychological theory of positive reinforcement with the application of some elements of psychological training, During seven lessons a considerable improvement of all components of joint activities was achieved, the transfer of worked out directions and abilities of improved group activities to new situations being verified.